Do You Trust ChatGPTs? Effects of the Ethical and Quality Issues of Generative AI on Travel Decisions - Kim, JH; Kim, J; Kim, C; Kim, S (Informa UK Limited, 2024)
This study investigated the impact of ChatGPT’s recommendation quality and ethical concerns on travelers’ acceptance, satisfaction, and perceived trustworthiness. Results showed that when quality and ethical concerns were prominent, acceptance of and satisfaction with ChatGPT’s recommendations decreased significantly, and the negative effects were mediated by perceived trustworthiness. This study also identified that message framing containing ChatGPT’s errors, and the information types delivered by ChatGPT, acted as moderators of the positive effect of its recommendations. These findings underscore the significance of addressing ethical and quality concerns in using AI (Artificial intelligence)-powered chatbots, with implications for AI acceptance and satisfaction.
Keywords: 35 Commerce, Management, Tourism and Services; 3506 Marketing; 3507 Strategy, Management and Organisational Behaviour; Behavioral and Social Science; Basic Behavioral and Social Science; 1504 Commercial Services; 1505 Marketing; 1506 Tourism; Marketing; 3504 Commercial services; 3506 Marketing; 3508 Tourism